KEBERSAMAAN QUR’ANY: UPAYA MEMBERDAYAKAN DAN MEMBAHAGIAKAN STAKEHOLDER SEKOLAH DASAR ISLAM TERPADU (SDIT) TUNAS HARAPAN ILAHI (THI), TANGERANG - Akhmad Shunhaji; Windy Dian Sari (Sekolah Tinggi Agama Islam Al Hidayah, 2022)
This paper aims to find a model of togetherness carried out by the Integrated Islamic Elementary School (SDIT) Tunas Harapan Ilahi (THI) Tangerang The togetherness carried out is analyzed in depth in order to obtain concrete data that the togetherness has a positive impact. The analysis is carried out with a phenomenological qualitative approach. The results of this study show that SDIT THI has designed a learning program, the togetherness of stakeholders and made improvements every school year. The togetherness practiced is in line with the teachings of the Qur'an. Happiness and empowerment can be obtained in learning activities and outside of learning. The results of empowered happiness have been felt by educators and education staff who have worked for more than two years. However, it is recognized by the leadership that empowering and happy togetherness needs to continue to be achieved properly. Another finding is that there are two important things that need to be considered so that SDIT THI continues to be the educational institution of choice for prospective parents. First, the developer of activities according to the activities of the learners. Second, periodic evaluation of activities.